(untitled) (Research, Society and Development, 2021)
The communication identity creation in organizations allows economic and / or administrative approaches discussion, and therefore, achievement of competitive advantages. When considering the Higher Education Institutions context and the growing concern with their development and assessment, their communication with stakeholders is valued. In this sense, this study aimed to analyze, based on the employee’s view, the internal and external communication of a Higher Education Institution in São Paulo, with an emphasis on creating competitive advantage. A structured electronic questionnaire was prepared, which was sent to all professionals at a Higher Education Institution located in São Paulo interior, obtaining 32 participations. The results showed that communication is a link that keeps the Higher Education Institution connected with its collaborators and with the external environment. In addition, components that could interfere with the organization’s internal and external communication was identified.